2020
DOI: 10.1177/0269215520961654
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted training after proximal humeral fracture: A randomised controlled multicentre intervention trial

Abstract: Objective: To examine whether robotic-assisted training as a supplement to usual therapy is safe, acceptable and improves function and patient reported outcome after proximal humeral fractures (PHF). Design: Multicentre, assessor-blinded, randomised controlled prospective trial. Setting: Three different rehabilitation hospitals in Germany. Subjects: In total 928 PHF patients between 35 and 70 years were screened. Forty-eight participants were included in the study (intervention group n = 23; control group n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this context, robot-assisted training has been developed in neurorehabilitation [21][22][23][24][25]. A meta-analysis by Chen et al [20] showed that robot-assisted training provided better outcomes for motor impairment disability compared to therapist-assisted training and no inferior outcomes for upper limb capacity, activity of daily living and social participation after stroke.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, robot-assisted training has been developed in neurorehabilitation [21][22][23][24][25]. A meta-analysis by Chen et al [20] showed that robot-assisted training provided better outcomes for motor impairment disability compared to therapist-assisted training and no inferior outcomes for upper limb capacity, activity of daily living and social participation after stroke.…”
Section: Introductionmentioning
confidence: 99%